Optimasi Biaya Distribusi Pengiriman Beras Sejahtera pada Perum Bulog Divisi Regional Sumatera Barat dengan Kombinasi North West Corner Method (NWCM) dan Stepping Stone Method (SSM) - Yeni Feriza; Dewi Murni (UNIVERSITAS NEGERI PADANG, 2020)
Abstract — The problem that the transportation model wants to solve is the determination of the distribution of goods which will minimize the total cost of distribution. Perum Bulog of the West Sumatra Regional Division as the executor of the prosperous rice program for several regions spent quite large funds for distribution activities, one of which was distribution in Padang Pariaman Regency. A transportation method is needed to find the best solution of the transportation problem (transportation), which are NWCM and SSM. NWCM as an initial method serves to determine the initial distribution allocation which will make all resource capacity allocated to all destinations, while SSM is an optimization test. The results of the calculation of the cost of distribution with NWCM are IDR27,967,340. Continued by an SSM of IDR 25,227,010. While the total real cost is, So that the calculation of the cost of distributing prosperous rice delivery using SSM is the optimum cost, the company can save transportation costs by IDR 3,335,130 or by 12%. Keywords — NWCM, SSM, Distribution fees.